P-209 Combined oncology and palliative care clinics; hospice in-patient stays and place of death (part 2). Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Gibbins, Jane; Benham, Beccy; Broadbent, Anna; Mader, Amman; Campbell, Carolyn; Newman, Rachel; Stevens, Deborah; Palmer, Joanne
Abstract : Background: Early Specialist Palliative Care (SPC) introduced to patients with advanced lung cancer has recently been proven to enhance quality-of-life and improve survival. Combined Oncology and Palliative Care Clinics (COPCC) have been carried at Royal Cornwall Hospital Trust for over two decades, to enable patients to be reviewed by palliative care consultants whilst attending the Oncology Centre; facilitating the two specialities to run in parallel to improve patient care. The aims of this project were to explore the use of inpatient hospice facilities of all patients, and place of death those for those patients who died. Methods: A retrospective case note review of 150 consecutive patients reviewed between 01/2016–06/2016. Data collected by three medical students. Results: Admissions to hospice: 18/150 patients (12%) had at least one hospice admission, with the most common primary reason for admission being symptom control (83%). Total number of admissions of any one patient ranged from one to seven. Length of stay from one to 46 days, with a median value of nine days. 11/18 admitted patients died during their most-recent hospice admission, and seven were discharged home. Place of death: 29/150 (19%) patients died at the time of data collection; 12 (41%) died at home, 11 (38%) died in a hospice, 6 (21%) died in acute (3/10.5%) or community hospital (3/10.5%). Conclusion: Access to SPC in COPCCs appears to enable early contact with inpatient hospice units, and enable more patients to die in the hospice and at home. 38% of this study's deceased patients died in a hospice; a 2.3 fold increase compared to hospice deaths of cancer patients specifically (16.4%). The number of deaths is small and warrants further studies.